Static and functional ultrasonographic picture shoulder and acromioclavicular joints in normal and at hypermobility. - Litvin, Yu. P.; Spuzyak, M. I.; Logvinenko, V. V.; Nekhanevich, O. B. (Морфологія / Morphologia / Morfologìâ, 2012)
Studying of anatomy humeral and acromioclavicular joints according to static and functional ultrasonography in norm and at hypermobility was an objective of this research. For the decision of an object in view we had been surveyed 45 persons at the age from 15 till 59 years (middle age has made 32,4±1,6 year), from them 32 men and 13 women. To clinical signs of hypermobility an investigated contingent have divided on two groups: the basic – 15 patients and control – 30 patients. It is established that humeral and acromioclavicular joints on ultrasonograms the features have display of elements. In research are described not changed soft tissue and bone structures, and also variants of their normal structure. By means of functional ultrasonography the basic signs of instability humeral and acromioclavicular joints have been defined.